2023
DOI: 10.3389/fped.2023.1043350
|View full text |Cite
|
Sign up to set email alerts
|

Safety and adherence of pressure garment therapy in children with upper limb unilateral cerebral palsy. Results from a randomized clinical trial ancillary analysis

Abstract: BackgroundThis study was conducted to assess the safety and adherence of the use of a PGT (Pressure Garment Therapy) Lycra® sleeve to treat upper limb unilateral cerebral palsy (UCP) in children.MethodsThis study was conducted as a prospective, placebo-controlled, double-blinded, randomized monocenter study. Included in the study were 58 UCP children, 49 of whom were analyzed. 25 children (mean age 6.6 ± 1.6 years; 12 girls) were allocated to the active group vs. 24 (mean age 6.7 ± 1.6 years; 10 girls) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In this study, wearing time and possible adverse events were recorded daily by the child's parents. The study results stated that the orthosis's daily wearing time was good, and the rate of adverse events was very low [37]. In this study, the time the child wore the orthosis in each evaluation session was reported by the child's parents, and the adverse effects caused by the orthosis were not reported either.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, wearing time and possible adverse events were recorded daily by the child's parents. The study results stated that the orthosis's daily wearing time was good, and the rate of adverse events was very low [37]. In this study, the time the child wore the orthosis in each evaluation session was reported by the child's parents, and the adverse effects caused by the orthosis were not reported either.…”
Section: Discussionmentioning
confidence: 67%